Hydride units filled boron–carbon clathrate: a pathway for high-temperature superconductivity at ambient pressure - Ying Sun; Li Zhu (Communications Physics, 2024)
Abstract Recent advances in the search for room-temperature superconductors have focused on high-temperature superconductivity in compressed hydrides, though sustaining this at ambient pressure remains challenging. Concurrently, s p 3-bonded frameworks comprising lightweight elements offer another avenue for ambient-pressure superconductors. However, their critical temperatures (T c) still fall short of those in hydrides. Here we propose a design strategy for achieving high-temperature superconductivity at ambient pressure by integrating hydride units into B–C clathrate structures. This approach exploits the beneficial properties of hydrogen, the lightest element, to enhance superconductivity beyond that of the parent compounds. Our computational predictions indicate that doping SrB3C3 with ammonium (NH4) produces SrNH4B6C6, with an estimated T c of 85 K at ambient pressure—over twice that of its precursor (31 K). Further substitutions yield a family of MNH4B6C6 superconductors, with PbNH4B6C6 predicted to reach a T c of 115 K. These findings offer a promising route to high-T c superconductors at ambient pressure.